Taking the Perceptual Analogy Seriously - Milona, Michael (Ethical theory and moral practice, 2016)
This paper offers a qualified defense of a historically popular view that I call sentimental perceptualism. At a first pass, sentimental perceptualism says that emotions play a role in grounding evaluative knowledge analogous to the role perceptions play in grounding empirical knowledge. Recently, András Szigeti and Michael Brady have independently developed an important set of objections to this theory. The objections have a common structure: they begin by conceding that emotions have some important epistemic role to play, but then go on to argue that understanding how emotions play that role means that there must be some alternative, emotion-independent route to obtaining knowledge of value. If there has to be such an emotion-independent route, then the perceptual analogy breaks down in a significant way. In this paper, I argue that the right ways for sentimental perceptualists to respond to each of these objections are revealed by thinking through how analogous objections applied to perception and the empirical domain would be answered. Although Szigeti's and Brady's objections should not persuade sentimental perceptualists to give up their view, the objections do put important constraints on what a form of the view has to be like in order to do exciting metaethical work.